Papal Infallibility: A Protestant Evaluation of an Ecumenical Issue - Powell, Mark E. (Grand Rapids, Mich. William B. Eerdmans Pub Co, 2009)
"The dogma of papal infallibility has become increasingly problematic for Roman Catholics, and it is a major point of division in Christian ecumenical dialogue - arguably the key issue separating Catholics and other Christians today. Mark Powell here co
Keywords: Catholic Church -- Doctrines. Catholic Church -- Teaching office. Catholic Church -- Infallibility